Targeting prostate cancer cells with enzalutamide‐HDAC inhibitor hybrid drug 2‐75. Issue 10 (28th May 2019) - Hu, Wen‐Yang; Xu, Liping; Chen, Bailing; Ou, Siyu; Muzzarelli, Kendall M.; Hu, Dan‐Ping; Li, Ye; Yang, Zhe; Vander Griend, Donald J.; Prins, Gail S.; Qin, Zhihui
Abstract: Background: The progression of castration‐resistant prostate cancer (CRPC) still relies on the function of androgen receptor (AR), achieved by evolving mechanisms to reactivate AR signaling under hormonal therapy. Histone deacetylase inhibitors (HDACis) disrupt cytoplasmic AR chaperone heat shock protein 90 (Hsp90) via HDAC6 inhibition, leading to AR degradation and growth suppression of prostate cancer (PCa) cells. However, current HDACis are not effective in clinical trials treating CRPC. Methods: We designed hybrid molecules containing partial chemical scaffolds of AR antagonist enzalutamide (Enz) and HDACi suberoylanilide hydroxamic acid (SAHA) as new anti‐PCa agents. We previously demonstrated that Enz‐HDACi hybrid drug 2‐75 targets both AR and Hsp90, which inhibits the growth of Enz‐resistant C4‐2 cells. In the current study, we further investigate the molecular and cellular actions of 2‐75 and test its anti‐PCa effects in vivo. Results: Compared with Enz, 2‐75 had greater AR antagonistic effects by decreasing the stability, transcriptional activity, and nuclear translocation of intracellular AR. In addition to inhibition of full‐length AR (FL AR), 2‐75 downregulated the AR‐V7 variant in multiple PCa cell lines. Mechanistic studies indicated that the AR affinity of 2‐75 retains the drug in the cytoplasm of AR + PCa cells and further directs 2‐75 to the AR‐associated protein complex, which permits localized effects on AR‐associated Hsp90. Further, unlike pan‐HDACi SAHA, the cytoplasm‐retaining property allows 2‐75 to significantly inhibit cytoplasmic HDAC6 with limited impact on nuclear HDACs. These selective cytoplasmic actions of 2‐75 overcome the unfavorable resistance and toxicity properties associated with classical AR antagonists, HDACis, and Hsp90 inhibitors. Finally, 2‐75 showed greater antitumor activities than Enz in vivo on SQ xenografts derived from LNCaP cells. Conclusions: Novel therapeutic strategy using newly designed 2‐75 and related AR antagonist‐HDACi hybrid drugs has great potential for effective treatment of CRPC.